JOINT MODELING FOR FACIAL RECOGNITION (2013)
This disclosure describes a system for jointly modeling images for use in performing facial recognition. A facial recognition system may jointly model a first image and a second image using a face prior to generate a joint distribution. Conditional joint probabilities are determined based on the joint distribution. A log likelihood ratio of the first image and the second image are calculated based on the conditional joint probabilities and the subject of the first image and the second image are verified as the same person or as different people based on results of the log likelihood ratio.